Kan landskapsarkitektur ses som konst? - Larsson, Petter (2008)
Comparing your own work with art has been an obvious standpoint for landscape architects, especially during the midst of the 20th century. With this as background this essay intends to find out if there are any change to this condition visible today. This essay discusses the two notions of "landscape architecture" and "art" with the intention of describing what they mean. A connection to todays active landscape architects is given through an examinating part of the essay. Four offices of landscape architecture is given the opportunity to communicate through their websites. How they portrait themselves is examined in order to understand how their vocabulary when selling their products. The conclusion of the essay presents an attempt to compare the lessons learned from the discussion parts with the examination of the websites.